Is There a Diversity of Dependent Capitalisms in Latin America? - Ilán Bizberg (Revue de la Régulation)
The Latin American continent has been considered as a paradigm of dependent economies since the studies of the Dependency Theory in the sixties and seventies. That is why a study of this continent is a significant contribution to this particular issue of the Revue de la Regulation. Nonetheless, our main presupposition is that although the Latin American countries are all more or less dependent, we cannot characterize them equally. That is why in this article we propose a typology of the different types of capitalism that have been dominant in this continent. In order to construct our typology we consider six analytical dimensions that are central for the regulation theory: 1. The accumulation regime: what a country produces, how it produces it and the manner in which it redistributes wealth between profits and wages; 2. The international insertion; 3. The role of the State; 4. The dominant social coalition, especially the place that civil society occupies in it; 5. The state structure (federalism and centralization) and the political system; and finally 6. the social contract/ the wage regime that results of the interaction of the former five dimensions.